2022
DOI: 10.21608/adjalexu.2022.111046.1238
|View full text |Cite
|
Sign up to set email alerts
|

Osseodensification by Densah Burs Versus Osteotome for Transcrestal Maxillary Sinus Lifting With Simultaneous Implant Placement

Abstract: INTRODUCTION:Implant placement in the posterior maxilla is problematic, not only due to inferior properties of bone but also due to loss of vertical bone height which happens after extraction of posterior teeth. When the required additional height is few millimeters, indirect transcrestal sinus lifting procedures is recommended. This study was carried out to compare clinically transcrestal sinus lifting with Densah burs versus osteotome with simultaneous implant placement. MATERIALS AND METHODS:This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…It is evident from the obtained results that the Densah group shows the highest mean implant primary stability; the osteotome group shows a lower mean value, and the piezosurgery group shows the lowest mean implant primary stability. This finding is similar to those of other studies [30,31] that demonstrated the highest implant stability to characterize the Densah group. However, our finding contradicts other studies that reported no significant difference concerning primary stability between the Densah and osteotome techniques [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…It is evident from the obtained results that the Densah group shows the highest mean implant primary stability; the osteotome group shows a lower mean value, and the piezosurgery group shows the lowest mean implant primary stability. This finding is similar to those of other studies [30,31] that demonstrated the highest implant stability to characterize the Densah group. However, our finding contradicts other studies that reported no significant difference concerning primary stability between the Densah and osteotome techniques [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…19 El-Ghobashy also reported these results in 2022. 12 A few studies highlighted the critical condition and achieved proper CSFE utilizing osseodensification sinus elevation. In 2021, Salgar demonstrated a few cases of crestal window approach using Densah sinus lift protocols to substitute lateral window technique in hyper-pneumatized posterior maxilla with a RBH < 1.5 mm and then augmented the sinus with bone grafting up to 15 mm with simultaneous implant placements.…”
Section: Densah Sinus Liftmentioning
confidence: 99%
“…[6][7][8][9][10] Common CSFE includes utilizing osteotomes, piezosurgical units, SCA kits, CAS kits, DASK system, and novel osseous densification kits named Densah burs. 1,3,8,[11][12][13][14] CSFE via Densah burs was first proposed by Huwais et al in 2018. 11 These specific burs compact autogenous grafting during the osteotomy in a counterclockwise motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations